Assessment of displacements in reinforced concrete buildings for the operation of 5G antennas in Chile (Gaceta Técnica, 2020)
The imminent emergence of 5G networks in the Chilean telecommunications market has made it essential to anticipate the possible imbalances that these could reach when any of the earthquakes that repeatedly strike the country occurs. To do this, a methodology based on conventional linear elastic analysis, both spectral modal and time-history, has been formulated to estimate the induced displacements for two different levels of strong ground movements, based on seismic records obtained in the subduction zone. The results obtained have served to obtain fairly adjusted analytical expressions, formulated from a single system variable, the height of the level, so that they can be used to quickly estimate the lateral displacements of the 5G antennas that will be networked, by personnel who has no training in structural dynamics, but who will be in charge of making the adjustments in the 5G network nodes
Keywords: 5G communication networks; lateral displacements; accidental regulatory charges; numerical simulation